An Enzyme Cascade Synthesis of ε-Caprolactone and its Oligomers - Schmidt, Sandy; Scherkus, Christian; Muschiol, Jan; Menyes, Ulf; Winkler, Till; Hummel, Werner; Gröger, Harald; Liese, Andreas; Herz, Hans-Georg; Bornscheuer, Uwe T. (Angewandte Chemie International Edition, 2015)
Schmidt S, Scherkus C, Muschiol J, et al. An Enzyme Cascade Synthesis of ε-Caprolactone and its Oligomers. Angewandte Chemie (International ed. in English) . 2015;54(9):2784-2787. Poly-ε-caprolactone (PCL) is chemically produced on an industrial scale in spite of the need for hazardous peracetic acid as an oxidation reagent. Although Baeyer-Villiger monooxygenases (BVMO) in principle enable the enzymatic synthesis of ε-caprolactone (ε-CL) directly from cyclohexanone with molecular oxygen, current systems suffer from low productivity and are subject to substrate and product inhibition. The major limitations for such a biocatalytic route to produce this bulk chemical were overcome by combining an alcohol dehydrogenase with a BVMO to enable the efficient oxidation of cyclohexanol to ε-CL. Key to success was a subsequent direct ring-opening oligomerization of in situ formed ε-CL in the aqueous phase by using lipase A from Candida antarctica, thus efficiently solving the product inhibition problem and leading to the formation of oligo-ε-CL at more than 20 g L(-1) when starting from 200 mM cyclohexanol. This oligomer is easily chemically polymerized to PCL.